ANALYZING THE DOUBLE BURDENS OF WOMEN WORKERS DURING COVID-19 PANDEMIC (CASE STUDY AT THE OFFICE OF BPJS KETENAGAKERJAAN BALI DENPASAR) - Rian Farandi Kisnugraha; I.G.N. Putra Suryanata (SEAN Institute, 2022)
Women workers are a group hit by the pandemic of Covid-19. This pandemic brings new roles for women workers in the personal and professional lives making the responsibilities are getting bigger. This research aimed at analyzing the double burdens faced by the women workers, especially those who are working at the office of BPJS Ketenagakerjaan Bali Denpasar. Specifically, it aimed at finding out the problems faced in doing the double burdens in the pandemic situation and the strategies applied to balancing the roles. This was qualitative study in which the data were collected through interviews with nine respondents. The data were analyzed qualitatively. Based on the results of analysis, it was found out that the respondents did not find any problems in doing the roles since there were supports from the family and the company. To balancing the roles, the respondents applied strategies that are (1) communicating and cooperating with the family, (2) hiring maids, (3) applying limitation of time for each activity, and (4) creating priority lists. Even though, the respondents had double or more burdens, but they did not face any serious problems because of the supports of the family, company, and other parties.